2015
DOI: 10.12661/pap.2015.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drying and storage conditions in the quality of sunflower seeds

Abstract: The viability of seeds passing through the appropriate conditions of harvest and post-harvest storage and the step. The objective of this study was to evaluate the physiological potential of sunflower seeds under different storage conditions (25 °C and 50%, 20 °C and 60%, 30 °C and 40% RH air) using different packages (permeable and impermeable). Physiological assessments were carried seeds in zero, three and six months of storage times and analyzed by the average test were compared by Tukey test at 5% probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
(9 reference statements)
2
8
0
1
Order By: Relevance
“…The results shown in Figure 3 confirm the inverse relation existing between the sensory quality of coffee and the values of electrical conductivity, potassium leaching, and free fatty acid contents, which is in agreement with various studies that showed similar results (CORADI et al, 2007;ISQUIERDO et al, 2011;MARQUES et al, 2008).…”
Section: Borém F M Et Al 165supporting
confidence: 90%
See 1 more Smart Citation
“…The results shown in Figure 3 confirm the inverse relation existing between the sensory quality of coffee and the values of electrical conductivity, potassium leaching, and free fatty acid contents, which is in agreement with various studies that showed similar results (CORADI et al, 2007;ISQUIERDO et al, 2011;MARQUES et al, 2008).…”
Section: Borém F M Et Al 165supporting
confidence: 90%
“…Yet other analyses, such as determination of electrical conductivity, potassium leaching, reducing and non-reducing sugars, and free fatty acids, among other aspects, can be carried out to assist understanding of physiological changes and changes in chemical composition that occur in coffee during the drying process (CORADI et al, 2007;GUIMARÃES et al, 2002;ISQUIERDO et al, 2012;KLEINWÄCHTER;SELMAR, 2010;MARQUES et al, 2008;SIQUEIRA et al;2016;SPEER;KÖLING-SPEER, 2006;TAVEIRA et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Coffee quality is associated to a set of factors that involve physico-chemical and sensorial aspects which, in turn, depend on the post-harvest handling and processing (Coradi et al, 2007;Afonso Júnior, 2001, Lima et al, 2008. Wet processing is more commonly preferred than the dry method due to its production of good quality coffee.…”
Section: Introductionmentioning
confidence: 99%
“…After drying and storing the grains, soybeans and sunflower oil were extracted to determine their yield and acid number. The Soxhlet extraction method was used to extract the oil (Coradi, Fernandes, Peralta, & Pereira, 2015). To analyze the oil yield, sunflower grains were ground with the aid of a domestic multiprocessor (model Pro Arno).…”
Section: Methodsmentioning
confidence: 99%